The Use of Gagne’s Model in Introducing Geometric Shapes to Intellectual Disability Children with Hearing Loss - Basudewa, Adly Haqi Agung; Suparmi, Suparmi (PSIKODIMENSIA, 2024)
Intellectual disability children with hearing loss, due to limitations in intellectual and hearing functions, had difficulty understanding geometric shapes. Therefore, an effective learning model was needed to teach these concepts. This study aimed to introduce geometric shapes (circles, squares, and triangles) to intellectual disability children with hearing loss. The hypothesis proposed was that using Gagne’s model would affect the ability to recognize geometric shapes, specifically circles, squares, and triangles, in intellectual disability children with hearing loss. This study was a single-subject research study with an A-B-A design. The measuring instrument used in this study was a checklist method filled in by the researcher. The participant was a 5-year-11-month-old girl diagnosed with mild intellectual disability and hearing loss, who attended an inclusive playgroup. The research procedure lasted for 21 sessions, consisting of three baseline sessions, 15 intervention sessions, and three maintenance sessions. The data analysis technique in this study used descriptive techniques from graphs. The results of this study indicated that Gagne’s model method was effective in introducing geometric shapes. Based on these results, the hypothesis was accepted, indicating that using Gagne’s model influenced the ability of intellectual disability children with hearing loss to recognize geometric shapes. The implication of this study was that Gagne’s model could be applied to intellectual disability children with hearing loss to teach geometric shapes effectively.